Nagel's reduction theory revisited - Ribeiro, Henrique de Morais [UNESP] (Univ Federal Ceara, Geography Posgraduate Program, 2019)
The aim of this paper is to develop further a model of reduction derived from Nagel's model and from the deductive-nomological model of explanation. We propose this development by examining its consistency with the history of physics, in particular, with Nagel's further account of the history of physics. In the first part, we introduce the issue of intertheoretical reduction. In the second, we examine the partial consistency of the derived D-N model of reduction with Nagel's further considerations on reduction. As a conclusion, we argue that, in agreement with Nagel's theory, the full consistency with history of science is a criterion needed for any purported theory of reduction and that the autonomy of the reducing science is to be preserved.
Keywords: Intertheoretical reduction; Nagel; Scientific explanation